The twelfth-century Translation and Miracles of St Guthlac - Sharpe, R (Paul Watkins Publishing, 2017)
The remains of St Guthlac at Crowland were translated in 1136, but apart from brief entries in chronicles the source describing this event was not written until (it is argued here) 1164, when style mattered more to the author than conveying any clear idea of what was done. The text of the Translatio cum miraculis, printed in 1675, has been neglected for centuries. The medieval text is restored and translated with commentary on its author’s literary sources. It provides glimpses of a rich cult but no meaningful historical context.